2010
DOI: 10.1186/1824-7288-36-57
|View full text |Cite
|
Sign up to set email alerts
|

Autoinflammatory syndromes: diagnosis and management

Abstract: During the last decades the description of autoinflammatory syndromes induced great interest among the scientific community. Mainly rheumatologists, immunologists and pediatricians are involved in the discovery of etiopathogenesis of these syndromes and in the recognition of affected patients. In this paper we will discuss the most important clues of monogenic and non-genetic inflammatory syndromes to help pediatricians in the diagnosis and treatment of these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 51 publications
1
32
0
1
Order By: Relevance
“…Familial Mediterranean Fever (FMF) is a prototypic auto-inflammatory disease characterized by recurrent febrile attacks accompanied with inflammation of the serosal membranes and of the skin and is prevalent among Mediterranean populations. The disease is due to mutations of the Mediterranean Fever Gene (MEFV), which is located in the short arm of the chromosome 16 (16p13.3) (De Sanctis et al, 2010;Zadeh et al, 2011). MEFV consists of ten exons and encodes the protein pyrin, which is involved in caspase-1 activation and consequently in interleukin-1β release.…”
Section: Introductionmentioning
confidence: 99%
“…Familial Mediterranean Fever (FMF) is a prototypic auto-inflammatory disease characterized by recurrent febrile attacks accompanied with inflammation of the serosal membranes and of the skin and is prevalent among Mediterranean populations. The disease is due to mutations of the Mediterranean Fever Gene (MEFV), which is located in the short arm of the chromosome 16 (16p13.3) (De Sanctis et al, 2010;Zadeh et al, 2011). MEFV consists of ten exons and encodes the protein pyrin, which is involved in caspase-1 activation and consequently in interleukin-1β release.…”
Section: Introductionmentioning
confidence: 99%
“…The Nijmegen patient registry was initiated in 1992 and holds data on more than 200 patients (http://www.hids.net) [13,14]. Population genetic studies in the Netherlands suggested a disease incidence between 1 in 5,196 and 1 in 53,656.…”
Section: Discussionmentioning
confidence: 99%
“…In children with a suspicion of a periodic fever syndrome, an accurate clinical history and a physical examination remain the first diagnostic tools [14]. Clinical vigilance in combination with a diagnostic strategy including close interaction between clinicians, laboratories, and geneticists is fundamental to diagnose patients with AID [11,27].…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab may worsen symptoms and should not be used. IL‐1 inhibition may be useful when other agents are ineffective . Up to 25% of those with TRAPS will develop amyloidosis …”
Section: Tnf Receptor‐associated Periodic Syndromementioning
confidence: 99%